Perancangan Sistem Informasi Paperless Office Dalam Distribusi Gambar Kerja Berbasis Web - Satria (Jurnal ICT: Information Communication & Technology, 2022)
PT. Surya Inti Alam is engaged in manufacturing Panel Making, Sheet Metal. The company has three main services/services for you, namely Electrical Installation Work, procurement of Electrical Panels and Indonesian sales representatives for Solutions Electrical Software products, providing Software for designing and calculating electrical systems. The problem so far is the distribution system of working drawings at PT. Surya Inti Alam still uses a semi-manual system, so many shortcomings are felt. The use of sheet paper for working drawings that are printed is too much so that it interferes with the smooth distribution which results in the loss of predetermined working drawings, another problem is the delay in the distribution of working drawings to the relevant departments so that problems arise, namely the frequent delays in achieving the production process targets. So designing a system by applying the concept of paperless office which aims to reduce the use of paper in the activities of the company. With the design of the Paperless Office information system, it facilitates the distribution process of Working Drawings in the form of a web-based Paperless Office and can accelerate and facilitate users in making reports that are more effective and neat.